Development of the Department of Veterans Affairs Centers of Excellence in Primary Care Education Trainee Participant Survey: Measuring Trainees’ Perceptions of an Interprofessional Education Curriculum - Davila, Jessica A.; Sansgiry, Shubhada; Rugen, Kathryn Wirtz; Rajashekara, Shruthi; King, Samuel; Amspoker, Amy; Tivis, Rick; Poppe, Anne; Harada, Nancy D.; Gilman, Stuart C. (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2021)
Background: The Trainee Participant Survey was developed for the evaluation of the Department of Veterans Affairs, Centers of Excellence in Primary Care Education (VA CoEPCE), which developed and delivered an interprofessional education (IPE) postgraduate curriculum to learners of multiple professions at seven geographically diverse VA facilities across the United States.Methods and findings: Perceptions of the curriculum by learners across professions were assessed to identify differences in curricular perceptions and unmet needs to inform programmatic changes. The comparison of responses by profession revealed no statistically significant differences across the core domains; precepting, supervising, mentoring; or program practices. Trainee professions differed significantly on satisfaction and system impacts.Conclusion: The Trainee Participant Survey has excellent psychometric properties and can serve as a model for evaluating future IPE programs.